Determinants Comparative Advantage of Non-Oil Export 34 Provinces in Indonesia - Irsan Hardi; Taufiq Carnegie Dawood; Putri Bintusy Syathi (Research Collaboration Community (RCC), 2021)
In spite of the country’s export activities constantly increase every year, based on the latest report Indonesia still sits at number 28th in the world's top export countries, consider Indonesia as one of the most populated nations and its rich natural resources. There is so much research in the literature about this issue, but to the author’s knowledge, there is still a lack of studies that analyze the performance of non-oil export comparative advantage between provinces in Indonesia instead of between its commodities. The purpose of this research is (1st) to compare non-oil exports comparative advantage between 34 provinces in Indonesia and (2nd) to prove the effect of chosen factors which are a foreign direct investment, local direct investment, inflation, interest rate, exchange rate, population, labor, minimum wage, education, income disparity, regional GDP, government expenditure, and GDP of importing country toward provinces comparative advantage of non-oil export. This research using provinces panel data years 2010-2019. The method of this study is Revealed Comparative Advantage (RCA) index and Trade Balance Index (TBI) to unveil non-oil export comparative advantage between 34 provinces in Indonesia and panel data regression to estimate the impact of determinant factors. The result of comparative advantage index estimation shows that 24 provinces have a comparative advantage based on the RCA index approach and 32 provinces have a comparative advantage based on the TBI approach on non-oil export activities year 2010-2019. The result of panel data regression found that 9 out of 13 determinant variables had a significant effect on the RCA index namely foreign direct investment, local direct investment, exchange rate, population, labor, minimum wage, income disparity, regional GDP, and government expenditure. Then 6 out of 13 determinant variables had a significant effect on TBI which are a local direct investment, interest rate, exchange rate, education, income disparity, and regional GDP.